2012
DOI: 10.1016/j.jsha.2011.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic importance of platelet parameters in patients with acute coronary syndrome admitted to a tertiary care hospital in southwest region, Saudi Arabia

Abstract: Platelet parameters mainly MPV and PDW are readily available and relatively simple and inexpensive laboratory tests which we detected to be significantly raised in patients who have suffered an acute coronary syndrome compared with controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 24 publications
5
27
0
1
Order By: Relevance
“…22 CAD occurs at any adult age, but it is the disease of middle and old age. In our study, the mean age of the patients in Group I (DM with CAD) was 54.73 (±8.94) years as compared to 56.59±13.63 years and 58.01±12.9 years, studies done by Assiri et al (2012) and Al-Saif et al (2011). It was 52.0±8.6 years in a study reported by Siddique et al (2010) and 56.6 years by Ullah M et al, (2011) in Bangladesh.…”
Section: Discussionsupporting
confidence: 39%
See 2 more Smart Citations
“…22 CAD occurs at any adult age, but it is the disease of middle and old age. In our study, the mean age of the patients in Group I (DM with CAD) was 54.73 (±8.94) years as compared to 56.59±13.63 years and 58.01±12.9 years, studies done by Assiri et al (2012) and Al-Saif et al (2011). It was 52.0±8.6 years in a study reported by Siddique et al (2010) and 56.6 years by Ullah M et al, (2011) in Bangladesh.…”
Section: Discussionsupporting
confidence: 39%
“…It was 52.0±8.6 years in a study reported by Siddique et al (2010) and 56.6 years by Ullah M et al, (2011) in Bangladesh. 21,[23][24][25] Mean total count of WBC was found 9.90 ± (1.91) x 10 9 /L in Group I and 8.66 ± (1.37) x 10 9 /L in Group II. This association is highly significant (p <0.001).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In our study, the mean age of the patients in Group I (patients with CAD) was 54.73 (±8.94) years as compared to 56.59±13.63 years and 58.01±12.9 years, studies done by Assiri AS et al, (2012) and Al-Saif SM et al, (2011). 16,17 It was 52.0±8.6 years in a study reported by Siddique MA et al, (2010) and 56.6 years by Ullah M et al, (2011) in Bangladesh. 18,19 There was clear male predominance in Group I (89.28%).…”
Section: Discussionmentioning
confidence: 84%
“…16,17 Despite improvement in primary prevention and treatment, CAD remains the chief cause of death in most developed countries. 18 e incidence is much greater in developing countries. 5 CAD occurs at any adult age, but it is the disease of middle and old age.…”
Section: Discussionmentioning
confidence: 99%